Di Bawah Dualisme Hukum : Komunitas Kristen Pribumi Jawa di Era Kolonial - Harto Juwono (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
This article aims to elucidate the legal status and position of indigenous Christian communities in Java during the colonial era. The reason for this is that their presence within the administrative and legal system of the Dutch East Indies necessitated clarity, given the frequent uncertainty in the implementation of Dutch government actions. As a historical work, this research employs historical sources inherited from past administrative activities, namely documents. Priority is given to primary documents, whether in the form of manuscripts or official publications, while reference sources will be used in accordance with their respective eras of creation. The data is obtained from archival repositories, both in the Netherlands and Indonesia, such as the National Archives of the Republic of Indonesia. The method used to process this data is the historical research method, which consists of four stages: heuristic, criticism, interpretation, and reconstruction. From the results of the reconstruction, it can be concluded that issues of interpretation are the main problem in addressing the aforementioned ambiguity. Differences in interpretation between indigenous Christian communities (and their missionary leaders) on one side and government authorities on the other side have led to disparities in policy implementation and even conflicts of interest. This situation is further exacerbated by the lack of clarity within the government apparatus itself in executing instructions, both at lower and higher levels, especially concerning indigenous Christian communities in Java. Abstrak Indonesia Artikel ini bertujuan untuk mengungkapkan status dan posisi hukum masyarakat pribumi Kristen di Jawa pada era kolonial. Alasan untuk hal ini adalah karena keberadaan mereka dalam sistem politik administrasi dan sistem hukum kolonial memerlukan kejelasan, mengingat seringkali terjadi ketidakpastian dalam penerapan tindakan pemerintah Hindia Belanda. Sebagai karya sejarah, penelitian ini menggunakan sumber sejarah yang merupakan warisan dari aktivitas administrasi masa lalu, yakni dokumen. Prioritas diberikan pada dokumen primer, baik berupa manuskrip maupun sumber resmi yang diterbitkan, sementara sumber referensi akan digunakan sesuai dengan era pembuatannya. Data-data tersebut diperoleh dari pusat penyimpanan arsip, baik di Belanda maupun di Indonesia, seperti di Arsip Nasional Republik Indonesia. Metode yang digunakan untuk mengolah data ini adalah metode penelitian sejarah yang terdiri atas empat tahap: heuristik, kritik, interpretasi, dan rekonstruksi. Dari hasil rekonstruksi, dapat disimpulkan bahwa persoalan interpretasi merupakan masalah utama dalam menjawab ketidakjelasan status di atas. Perbedaan interpretasi antara umat Kristen pribumi (dan para pendeta zendingnya) di satu sisi dan aparat pemerintah di sisi lain mengakibatkan perbedaan dalam aplikasi kebijakan dan bahkan dapat mengarah pada konflik kepentingan. Hal ini semakin memburuk akibat ketidakjelasan pada aparat pemerintah sendiri dalam melaksanakan instruksi baik di tingkat bawah maupun atas, khususnya terhadap komunitas Kristen pribumi di Jawa.